MUATAN LOKAL KE-NU-AN: Analisis Pembentukan Karakter Kebangsaan Peserta Didik Melalui Sejarah dan Kebudayaan Islam - Muhammad Abu Kholil (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2021)
The results of this study indicate that the LOCAL CONTENT OF THE NU-AN (Analysis of the Formation of National Characters of Students through SKI Material), namely: First, the development of NU's local content subject matter was developed in accordance with the conditions and conditions of the class and in accordance with the innovation in accordance with the themes and material to be delivered to students. Second, the national character that must be possessed by students through the subjects of NU's local content is the national character that is typical of the Indonesian people, namely polite, polite, friendly, greeting each other, nationalism, patriotism, love for the homeland, and tolerance. Third, the effectiveness of NU's local content subject to the formation of student national character through Islamic Cultural History material, this is very effective because Isam's Cultural History material in Islamic history in Indonesia pioneered by Walisongo, and Walisongo itself is one of the reasons Nahdhotul Ulama stands. The Nahdhotul Ulama was preached by using the Wali Songo method in spreading the teachings of Islam without leaving tradition and culture, and this was continued by the Nahdhotul Ulama until now. And from the example of the founding figures Nahdhotul Ulama can be embedded in students who are the next generation of the nation.